THE POWER OF SOCIAL MEDIA IN POLITICAL CAMPAIGN: AN ANALYSIS OF MALAYSIA’S GE 15 - Iman Anuar, Muhammad Nur; Hazwan Alias, Muhammad Naim; Aziera Rahim, Nur Aqilah; Indra Elpi, Nur Afiqah Izzati; Ramlan, Aini Faezah; Djuyandi, Yusa; Azmi, Mohammad Fazrulzaman (Universitas Padjadjaran, 2025)
This research explores the transformative impact of social media on political campaigns, particularly in the context of Malaysia’s 15th General Election (GE15). Social media platforms as a political campaigning tool highlight its influence on young voters and their perceptions of political figures. In addition, social media has revolutionized the dynamics of political engagement, it has also introduced challenges such as the spread of misinformation, hate speech, and unequal access among political parties. This research applied a qualitative method by comparing various literatures. Leveraging The Technology Acceptance Model (TAM), this study aims to analyze how social media influences election outcomes and shape public opinion. The findings reveal that social media played a significant role in GE15, with candidates strategically utilizing platforms like Facebook and TikTok to engage voters, especially the youth demographic. Ultimately, social media not only serves as a battleground for public discourse but also shapes the political landscape by reaching out to digital natives and first-time voters who rely on social media for news and information. This research contributes to the understanding of digital campaign dynamics by demonstrating how the perceived ease of use and usefulness of social media influence political campaigning. It underscores the critical role of technological acceptance in the adoption of new media strategies by political actors. By applying TAM, this study provides valuable insights into the power of social media in modern political campaigns, offering practical recommendations for political strategists and parties aiming to enhance their digital engagement and campaign effectiveness in future elections.